Using Analysis of Gini (ANOGI) for Detecting Whether Two Subsamples Represent the Same Universe: The German Socio-Economic Panel Study (SOEP) Experience - Joachim R. Frick; Jan Goebel; Edna Schechtman; Gert G. Wagner; Shlomo Yitzhaki (Sociological Methods & Research, 2006)
A wildly discussed shortcoming of panel surveys is a potential bias arising from selective attrition. Based on data of the German Socio-Economic Panel Study (SOEP), the authors analyze potential artifacts (level, structure, income inequality) by comparing results for two independently drawn panel subsamples started in 1984 and 2000. They apply ANOGI (analysis of Gini) techniques, the equivalent of ANOVA performed with the Gini coefficient. They rearrange, reinterpret, and use the decomposition in the comparison of subpopulations from which the different samples were drawn. Taking into account indicators for income, significant differences between these two samples with respect to income inequality are found in the first year, which start to fade away in Wave 2 and disappear in Wave 3. The authors find credible indication for these differences to be driven by changes in response behavior of short-term panel members rather than by attrition among members of the longer running sample.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; panel studies; survey research; inequality composition; Gini